ANALISIS KINERJA PENYULUH PERTANIAN DALAM MEMBERDAYAKAN DAN MEMANDIRIKAN PETANI KARET DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Marnalom Hutahaean; Rosnita Rosnita; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims 1) To determine the characteristic, the independent, and the characteristic of system sosial of agricultural extension worker insubdistrict Gunung Toar of Kuantan Singingi. 2) To analyzed the performance of agricultural extension workers in subdistrict Gunung Toar. 3) To analize the empowerment and independent of oil palm in Gunung Toar sub district of Kuantan Singingi. Research using survey method amounted to 5 extension selected by census and 55 non-pattern rubber farmers were chosen randomly. The Research analysed with scale likert. The results showed that 1) Characteristic extension workers in SubDistrict Gunung Toar categorized as